Hiding the Bodies: Geographic Repression in Higher Educational Space. Issue 4 (November 2019) - Richardson, Tina
This article critiques the way that universities have acquired and developed campus space since World War II. Prompted by the need to increase student entry, British universities grew exponentially, with a demand to expand the campus in order to provide more teaching space and student accommodation. This article looks at the side effects of this expansion by providing a case study that demonstrates that land acquisition can have a deleterious effect on local residents. Using theories from urban studies, postmodern geography and cultural theory, this article presents the case study through a transdisciplinary lens, offering an original analysis of the heritage of an inherited cemetery.